Rewrite the following equation in slope-intercept form.

y
+ 8
=
1
6
(
x
− 6
)

1 answer

To rewrite the equation \( y + 8 = \frac{1}{6}(x - 6) \) in slope-intercept form \( y = mx + b \), follow these steps:

  1. Distribute \( \frac{1}{6} \) on the right side: \[ y + 8 = \frac{1}{6}x - 1 \] (Since \( \frac{1}{6} \times -6 = -1 \)).

  2. Subtract 8 from both sides to isolate \( y \): \[ y = \frac{1}{6}x - 1 - 8 \]

  3. Combine the constant terms on the right: \[ y = \frac{1}{6}x - 9 \]

So the equation in slope-intercept form is: \[ y = \frac{1}{6}x - 9 \]